The Future of Medicine: Frontiers in Integrative Health and Medicine - Schneider, Robert H.; Seetharaman, Mahadevan (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Contemporary healthcare trends indicate that many chronic and communicable diseases are related to lifestyle, stress, personal choices and systemic factors. In response to the shortfalls of modern medicine regarding the prevention of these diseases and the promotion of whole-person health, providers and consumers worldwide are exploring integrative, natural and complementary approaches to prevention, treatment and health promotion. These trends harbor the future of medicine. The issues of clinician burnout, high rates of adverse effects, high cost, and lack of rigorous methods to promote individual and collective immunity are addressed by leading physicians and scientists from around the world. The original research and reviews in this volume investigate efficacy, molecular mechanisms and hypotheses that suggest that traditional systems of medicine and health, e.g., Ayurveda, yoga, traditional Chinese medicine, and mind-body-lifestyle medicine, may offer preventive and cost-effective solutions to contemporary health care challenges. Integrating innovative health approaches with conventional medicine offers a whole system of medicine that encompasses the individual, family, community and environment-from single person to planetary health.